2016
DOI: 10.3389/fnhum.2015.00710
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Music Therapy Training for Mobility and Stability Rehabilitation with Parkinson’s Disease – A Pilot Study

Abstract: Idiopathic Parkinson’s Disease (PD) is a progressive condition with gait disturbance and balance disorder as the main symptoms. Previous research studies focused on the application of Rhythmic Auditory Stimulation (RAS) in PD gait rehabilitation. The key hypothesis of this pilot study, however, assumes the major role of the combination of all three Neurologic Music Therapy (NMT) sensorimotor techniques in improving spatio-temporal gait parameters, and postural stability in the course of PD. The 55 PD-diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 39 publications
1
56
0
7
Order By: Relevance
“…Of these studies, two used MT for speech and language rehabilitation via melodic intonation therapy (MIT) [63,71] and modified-MIT in the form of the Speech Music Therapy for Aphasia (SMTA) program [58,72]. MT was additionally used for sensorimotor rehabilitation by combining rhythmic auditory stimulation (RAS), patterned sensory enhancement (PSE), and therapeutic instrumental music performance (TIMP) techniques into one clinical program [60,73,74].…”
Section: Neurologic Art Therapy Techniquesmentioning
confidence: 99%
“…Of these studies, two used MT for speech and language rehabilitation via melodic intonation therapy (MIT) [63,71] and modified-MIT in the form of the Speech Music Therapy for Aphasia (SMTA) program [58,72]. MT was additionally used for sensorimotor rehabilitation by combining rhythmic auditory stimulation (RAS), patterned sensory enhancement (PSE), and therapeutic instrumental music performance (TIMP) techniques into one clinical program [60,73,74].…”
Section: Neurologic Art Therapy Techniquesmentioning
confidence: 99%
“…Music engages a variety of brain areas involved in emotion, motivation, cognition, and motor skills, and musical input have been utilized to enhance socialization and cognitive, sentimental, and neuromotor operation (Raglio et al, 2015). Applied music, through its main elements -pitch, dynamics and harmony, meter, tempo and rhythm, allows the organization of movement in time and space, leads to movement fluency, provides impulses to muscles and supplies rhythmic instructions by which to initiate and maintain activity (Bukowska et al, 2016). Therefore listening to one's preferred music along with exercise can have a significant beneficial effect by improving one's autonomic balance.…”
Section: Resultsmentioning
confidence: 99%
“…Physiological data has proven that improvisatory music therapy modulates emotional arousal in patients with dementia. Studies on Alzheimer's patients have shown that stimulating the somatosensory system by way of music therapy produces significant improvement in behavioral and cognitive scales [34][35][36][37][38]. With an increase in ageing population these conditions are going to increase.…”
Section: Strokementioning
confidence: 99%